Association of Serum Phosphorus Concentration with Mortality and Graft Failure among Kidney Transplant Recipients - Jeon, Hee Jung (Clin J Am Soc Nephrol, 2017)
BACKGROUND AND OBJECTIVES: Hyperphosphatemia in kidney transplant recipients has been shown to predict poorer graft and patient survival. However, studies examining hypophosphatemia are scarce. DESIGN, SETTING, PARTICIPANTS, & MEASUREMENTS: To evaluate the association of serum phosphorus level with patient and graft survival, we performed a retrospective multicenter cohort study. Between January of 1997 and August of 2012, 2786 kidney transplant recipients (41.7±11.4 years; 59.3% men; 73.5% living donors; 26.1% with diabetes; 3.8% with prior history of cardiovascular disease) were classified into seven groups according to serum phosphorus levels 1 year after transplantation, with intervals of 0.5 mg/dl (lowest group, <2.5 mg/dl; highest group, ≥5.0 mg/dl; reference group, 3.5–3.99 mg/dl). Survival analysis was performed by defining baseline time point as 1 year after transplantation. RESULTS: During median follow-up of 78.5 months, 60 patient deaths and 194 cases of graft loss occurred. In multivariate analysis, both lowest and highest serum phosphorus groups were associated with higher mortality, compared with the reference group (hazard ratio [HR], 4.82; 95% confidence interval [95% CI], 1.36 to 17.02; P=0.01; and HR, 4.24; 95% CI, 1.07 to 16.84; P=0.04, respectively). Higher death-censored graft loss was observed in the lowest and highest groups (HR, 3.32; 95% CI, 1.42 to 7.79; P=0.01; and HR, 2.93; 95% CI, 1.32 to 6.49; P=0.01, respectively), despite eGFR exhibiting no difference between the lowest group and reference group (65.4±19.3 versus 61.9±16.7 ml/min per 1.73 m(2); P=0.33). Moreover, serum phosphorus showed a U-shape association with patient mortality and graft failure in restricted cubic spline curve analysis. CONCLUSIONS: Serum phosphorus level 1 year after transplantation exhibits a U-shape association with death-censored graft failure and patient mortality in kidney transplant patients characterized by relatively high rate of living donor transplant and low incidence of diabetes and prior cardiovascular disease compared with Western countries.